The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity. Issue 20 (16th June 2022) - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen K.; Keil, Waldemar; Kühne, Thomas D.; Tiemann, Michael
Abstract: In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom ('structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall‐to‐water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2 ) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2 O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall‐to‐water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface‐specific sum‐frequency generation calculation for pore environments. Abstract : The spatial confinement of silica mesopores (≈4 nm in diameter) restricts hydrogen bonding of water molecules. The strength of the wall‐to‐water interactions (i.e., pore wall polarity) alters the structure of water within the pores. Computations support the experimental findings and enable a deeper understanding of spectroscopic data. Interface interactions, coordination, and angular distribution of water are investigated.